Como o declínio e a perda da autoridade contribuíram para a ascensão do totalitarismo em Hannah Arendt? - Fernandes, Leandro Mateus (2016)
This dissertative academic work presents the central problematic about the authority crisis over the tradition of the western philosophical and political thought and its collapse by the totalitarian regime effectuation. Arendt relevantly analyses the notion of authority in Ancient Greek and Roman conceptions, and emphasizes that, in the greek conception, there is an establishment attempt of a beginning of authority of polis government, however, these attempts are summarized as exemples of private organization and it doesn’t concern to human and political subjects, which evokes an authoritarian government, since it touches the principles of political liberty and equality. The ancient Roman had the conception and practice of the authority about the human subjects, in other words, to the public scope, as a structure, which ensures permanence and durability to the government, which has support by the hierarquic relation of command and obedience in free agreement, in mutual recognition of respect between the governors and governed people. This relation of authority, which make governments long lasting in a deep meaning of sacrality of the establishment of the act, like in the ancient Rome, decreases, first as a loss of tradition that connects men to the past, because this tradition was used as a thrust of meaningfulness to presente and future life. Losing this connection with the past, men live in a future projection way and the emptiness of meaning is each time more loaded with the expectation that will come. The failure of traditions is followed by the loss of religion, which means men don’t put their faith in governments and politics anymore – institutions that don’t connect and reconnect men to a establishing principle that ensure authority, permanence and durability of governments anymore. After defeat of tradition and religion, the last one to be lost is the authority its own and its political meaningfulness of roman ways with the consolidation of the totalitarian regimes. These are considered, by Arendt, the most cruel and terrible political ways of all times. Totalitarianism is the absolute denial and destruction of everything an authority used to ensure some things to governments, such as permanence and durability, but mainly freedom of acting and equality. In politics, the denial of the distinct, men are needless, disposable, standardized, animalizes and have their lives denied with mass killing machines, produced in concentration fields. The desire of totalitarianism by the destruction of liberty and spontaneity is a peace graveyard, in which everything that is different and opposite to its goals must be destroyed or killed. Precisely by the fact that the total regime had been made effective in history like the most absolute denial of politics, analysing and understanding phenomenons that made it is truly important so this catastrosphic kind of politics don’t ever come back to happen. One of the ways of trying to stop its return, according to Arendt, is to consolidate a government structured by a establishing principle, having the origin of authority and allowance of liberty of the political acting.